2022
DOI: 10.3389/fnint.2022.815750
|View full text |Cite
|
Sign up to set email alerts
|

Neural Correlates of Multisensory Integration for Feedback Stabilization of the Wrist

Abstract: Robust control of action relies on the ability to perceive, integrate, and act on information from multiple sensory modalities including vision and proprioception. How does the brain combine sensory information to regulate ongoing mechanical interactions between the body and its physical environment? Some behavioral studies suggest that the rules governing multisensory integration for action may differ from the maximum likelihood estimation rules that appear to govern multisensory integration for many perceptu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Several studies have reported a dominant reliance on visual feedback during adaptation of reaching movements when vision and proprioception provide contradictory input signals ( Scheidt et al, 2005 ; Pipereit et al, 2006 ; Judkins and Scheidt, 2014 ). However, during dynamic perturbations of the limb when proprioception supplies important information to control and adapt movements, it can play a more prominent role compared with visual feedback ( Bock and Thomas, 2011 ; Suminski et al, 2022 ). In accordance with these latter findings, our results highlight a clear dominance of force feedback over visual feedback during adaptation.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported a dominant reliance on visual feedback during adaptation of reaching movements when vision and proprioception provide contradictory input signals ( Scheidt et al, 2005 ; Pipereit et al, 2006 ; Judkins and Scheidt, 2014 ). However, during dynamic perturbations of the limb when proprioception supplies important information to control and adapt movements, it can play a more prominent role compared with visual feedback ( Bock and Thomas, 2011 ; Suminski et al, 2022 ). In accordance with these latter findings, our results highlight a clear dominance of force feedback over visual feedback during adaptation.…”
Section: Discussionmentioning
confidence: 99%